Una experiencia de creatividad con adolescentes hospitalizados. Unidad de psiquiatría de adolescentes del Gregorio Marañón - Ávila, Noemí; Pascale, Pablo (Arte, Individuo y Sociedad, 2007)
The "Curarte project" is been developing by the Department of Art Didactic of the Complutense University of Madrid during the lasts years. The most important propose in this project is the "Design, application and evaluation of creative games and toys specially adapted for use in hospitals". In this new project the investigation group worked in the "Design and application of creatives and artistics activities" with hospitalized adolescents in the Community of Madrid. This proposal in concrete was developed in the Unit of Psychiatry of adolescents of the Gregorio Marañón Hospital in Madrid.